Factors associated with recent increase of multiple births in Spain - Fuster Siebert, Vicente (2008)
The increased incidence of multiple deliveries in Spain, in addition to changes in age at maternity and parity, is attributed to assisted reproductive treatments, but the relative contribution of the latter to this rise remains uncertain, due to the scarce information provided by clinics practicing those treatments. Population based data (1984-2004), including information on mother's age, nationality, marital status, date of delivery, and the characteristics of each (parity, single or multiple), and sex of newborns were provided by the Spanish Institute of Statistics. Twinning and triplet deliveries relate to maternal age, parity, and nationality. For younger ages (≤ 19, 20-24, 25-29) rates remained constant over time, but for older women (30-34, 35-39, ≥ 40) rates increased after 1994. From 1984 to 2004 the percentage of twins of opposite sex increased from 24.31 to 36.58 per cent. Since 1997, Spanish and non-Spanish mothers differentiate with respect to multiple maternity at ages over 30. In addition to unmarried Spanish women, immigrants constitute a reliable reference group that determines the convenience of segregating information on multiple deliveries respecting origin. The proportion of twins and triplets of opposite sex, maternal age, and parity patterns observed are concordant with a differential access to reproductive treatments depending on the woman's age. The present norm regulating the maximum number of fertilizations per cycle and the demand for these treatments explain the high incidence of multiple deliveries in Spain. A modified logistic curve predicts a stabilization of multiple deliveries, which will probably continue to be high in Spain.